Virus- and cell type-specific effects in orthohantavirus infection - Hägele, Stefan; Müller, Alexander; Nußhag, Christian; Zeier, Martin; Krautkrämer, Ellen (Virus research, 2019)
Orthohantaviruses Hantaan (HTNV) and Puumala (PUUV) virus cause hemorrhagic fever with renal syndrome (HFRS), that is characterized by acute renal failure with often massive proteinuria and by morphological changes of the tubular and glomerular apparatus. Orthohantaviral N protein is found in renal cells and plays a key role in replication. However, the replication in human renal cells is not well characterized. Therefore, we examined the orthohantaviral infection in different human renal cells. Differences in localization of N protein, release of particles, and modulation of the actin cytoskeleton between both virus species are observed in human renal cells. A substantial portion of HTNV N protein demonstrates a filamentous pattern in addition to the typical punctate pattern. Release of HTNV depends on an intact actin and microtubule cytoskeleton. In contrast, PUUV N protein is generally localized in a punctate pattern and release of PUUV does not require an intact actin cytoskeleton. Infection of podocytes results in cytoskeletal rearrangements that are more pronounced for HTNV. Analyzing Vero E6 cells revealed differences compared to human renal cells. The pattern of N proteins is strictly punctate, release does not depend on an intact actin cytoskeleton and cytoskeletal rearrangements are not present. No virus-specific variations between HTNV and PUUV are observed in Vero E6 cells. Using human renal cells as cell culture model for orthohantavirus infection demonstrates virus-specific differences and orthohantavirus-induced cytoskeletal rearrangements that are not observed in Vero E6 cells. Therefore, the choice of an appropriate cell culture system is a prerequisite to study orthohantavirus pathogenicity.